Spectral signature secured retrodirective array. Issue 4 (7th December 2016) - Fusco, Vincent; Ding, Yuan; Buchanan, Neil
Abstract : A novel retrodirective array (RDA) architecture is proposed which utilises a special case spectral signature embedded within the data payload as pilot signals. With the help of a pair of phase‐locked‐loop based phase conjugators the RDA's response to other unwanted and/or unfriendly interrogating signals can be disabled, leading to enhanced secrecy performance directly in the wireless physical layer. The effectiveness of the proposed RDA system is experimentally demonstrated.